(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
The aim of the present investigation was to develop and evaluate gastroretentive drug delivery tablets (GRDDTs) of ofloxacin using different polymers such as HPMC K4M, HPMC K15M, Polyethylene oxide WSR 303, Carbopol 971P, Xanthan Gum in different ratios for local action in gastric region to eradicate Helicobacter pylori infection. The GRDDTs were prepared by wet granulation method and evaluated for physical characteristics such as hardness, thickness, friability, drug content and floating properties. The optimized formula F4 showed better sustained drug release and which also had good floating properties and fitted best to be Korsmeyer-Peppas model with R2 value of 0.9848. As the n value for the Korsmeyer- Peppas model was found be less than 0.45 it follows Fickian diffusion mechanism. FT-IR result showed that there is no drug excipient interaction. In vivo radiographic studies were conducted with BaSO4 loaded tablets to examine the increased gastric residence time of the prepared tablets. The study revealed that the tablet remained in the stomach for 300±10min which indicates the increase in the gastric residence time for the effective localized action of the ofloxacin in the treatment of Helicobacter pylori caused peptic ulcer. Key words: Ofloxacin; Helicobacter pylori; gastric residence time; gastroretentive drug delivery system. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8861 SJPS 2011; 4(1): 9-18